Reducing Stigmas : How the South Korean Government Aims to Reduce Mental Health Stigmas and Stigma-based Discrimination? - Suomalainen, Eveliina (My University, 2021)
The study focuses on structural and public stigmas in South Korean mental health policy between 2016 and 2020. The aim of the study is to research what negative effects of stigmatization can be identified in the South Korean mental health policy, does the South Korean government identify them in the policy plan for 2016-2020, and what has been done to reduce the stigmas and stigma-based issues in the five-year policy period from 2016 to the end of 2020? Qualitative content analysis on previous literature, South Korean central government’s mental health plan for 2016 to 2020, statistical data, and law texts were conducted to answer the research questions. Based on previous literature, structural stigmas related to legislation, length of stays in hospitalization, welfare, and human rights were found, as well as issues related to public stigma in education, awareness, and media. The South Korean mental health plan for 2016 to 2020 was found to have policy goals and tasks to improve most of the stigma-based issues identified in previous literature. Based on changes in legislation, statistical data, and previous studies, improvements to structural stigmas regarding hospitalization, occupational rights of mentally ill, and the overall mental health legislation were found. Significant improvements to issues of public stigma were not found. Based on the findings it was concluded that improvements in legislation and human rights of the mentally ill were made, but many issues related to structural stigmas and public stigmas still remain, especially in community integration and media coverage of mentally ill persons and the issues need more attention and resources in future mental health plans.
Keywords: South Korea, mental health, structural stigma, public stigma